(En) Corps Sonore: towards a feminist ethics of the ‘idea’ of music in recent French thought - Hickmott, S (2017)
This thesis explores the way music is characterized, used, or accounted for in recent (post-1968) French thought, focusing in particular on the work of Jean-Luc Nancy, Philippe Lacoue-Labarthe, and Alain Badiou. In spite of the differences in their philosophical-theoretical positions, all of these writers invoke music – both directly and indirectly – to negotiate their relationship to ontological, political, ethical and aesthetic concerns, particularly in terms of how it relates to the (im)possibility of a subject, the condition of truth, and the role of philosophical thought itself. The thesis situates these texts in a longer genealogy of musico-philosophical interactions and also brings them into dialogue with recent musicological approaches, thus showing how an inherited idea of what music ‘is’ is often assumed rather than critically re-evaluated. In short, by tracing the musical-transcendental baggage of an inherited metaphysical conception of music – one which often understands music in close relation to the feminine, (sexual) excess, and the beyond of language and/or the symbolic – the thesis shows that though music is instrumentalized by progressive thinkers as a way of shifting theoretical/philosophical paradigms, it nonetheless does so in a way that has a strong sense of continuity with previous thinking on music. Secondly, the thesis highlights the way in which music in its metaphysical-ontological guise is often conceived as synonymous with Western high art classical music (which is itself constructed as absolute and transcendent, and ontologically independent of its means of (re)production or context) whilst non-literate, popular, folk and world musics – on the occasions that they are considered and not simply ignored or denigrated – are notably considered almost exclusively in terms of their social-cultural or technological contexts. Finally, the thesis demonstrates that much of this takes place through a simultaneous instrumentalization of gender as an organisational category for philosophy, and one which all too often has the consequence of sending women – along with music – to the beyond of pre-, inter-, or post-signification.